Emergence of a novel hybrid mcr-1-bearing plasmid in an NDM-7-producing ST167 Escherichia coli strain of clinical origin - Xia, Shuang; Wang, Wei; Cheng, Jing; Zhang, Tingting; Xia, Ziwei; Zhao, Xiaoyu; Han, Yungang; Li, Yonghong; Shi, Xiufang; Qin, Shangshang (Frontiers in Microbiology, 2022)
Colistin is considered as an antibiotic of ‘last resort’ for the treatment of lethal infections caused by carbapenem-resistant Enterobacterales (CRE), dissemination of plasmid-borne colistin resistance gene mcr-1, particularly into CRE, resulting in the emergence of strains that approach pan-resistance. A wide variety of plasmid types have been reported for carrying mcr-1. Among which, large IncHI2-type plasmids were multidrug-resistant (MDR) plasmids harbored multiple resistance determinants in addition to mcr-1. Herein, we characterized a novel hybrid IncHI2-like mcr-1-bearing plasmid in an NDM-7-producing ST167 Escherichia coli strain EC15-50 of clinical origin. Antimicrobial susceptibility testing showed E. coli EC15-50 exhibited an extensively drug-resistant (XDR) profile that only susceptible to amikacin and tigecycline. S1-PFGE, Southern hybridization and Whole-genome Sequencing (WGS) analysis identified a 46,161 bp blaNDM-7-harboring IncX3 plasmid pEC50-NDM7 and a 350,179 bp mcr-1-bearing IncHI2/HI2A/N/FII/FIA plasmid pEC15-MCR-50 in E. coli EC15-50. Sequence detail analysis revealed the type IV coupling protein (T4CP) gene was absent on pEC15-MCR-50, explaining that pEC15-MCR-50 was a non-conjugative plasmid. Comparative genetic analysis indicated the hybrid plasmid pEC15-MCR-50 was probably originated from pXGE1mcr-like IncHI2/HI2A/N plasmid and pSJ_94-like IncFII/FIA plasmid, and generated as a result of a replicative transposition process mediated by IS26. Currently, the prevalent mcr-1-carrying IncHI2 plasmids were rarely reported to be fused with other plasmids. The identification of the novel hybrid plasmid pEC15-MCR-50 in this study highlighted the importance of close surveillance for the emergence and dissemination of such fusion MDR plasmids, particularly in NDM-producing Enterobacterales.